(untitled) (KYAMC Journal, 2017)
Coriander is cultivated throughout the world for its nutritional value. The present study was undertaken with an objective to study the effects of oral administration of coriander on memory boosting and regaining. Here we investigated the influence of oral intake of coriander on behavioural task performance by using T-maze and radial arm maze and physiological measures relative to a milk control group. We have observed significant memory boosting and memory regaining effects of coriander when administered orally. This effect may be due to memory-improving property and anticholinesterase activity of coriander. Hence we recommend that coriander can be used as a remedy in the management of Alzheimer’s disease. KYAMC Journal Vol. 4, No.-2, Jan 2014, Page 398-401